2020
DOI: 10.2147/ott.s265372
|View full text |Cite
|
Sign up to set email alerts
|

<p>Estrogen-Related Receptor α (ERRα) and G Protein-Coupled Estrogen Receptor (GPER) Synergistically Indicate Poor Prognosis in Patients with Triple-Negative Breast Cancer</p>

Abstract: The present study aims to demonstrate the correlation between estrogen-related receptor α (ERRα) and G protein-coupled estrogen receptor (GPER) expression and its predictive role in the prognosis of patients with triple-negative breast cancer (TNBC). Methods: A retrospective review of 199 cases of TNBC was conducted to assess the GPER and ERRα expression, and its clinicopathologic and prognostic implications. Subsequently, the effects of ERRα and GPER on cell viability, migration, and invasion induced by estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…An in vitro study suggested that GPER-mediated estrogen-induced ERRα upregulation may promote TNBC cell viability, migration, and invasion. ERRα-GPER interactions lead to a malignant phenotype of TNBC, and this result was consistent with the conclusion drawn from the survival analysis ( Ye et al, 2020 ). Additional research is necessary to determine the potential mechanisms that contribute to the interplay between GPER and ERRα in TNBC.…”
Section: Mechanism Of Gper In Tnbcsupporting
confidence: 91%
“…An in vitro study suggested that GPER-mediated estrogen-induced ERRα upregulation may promote TNBC cell viability, migration, and invasion. ERRα-GPER interactions lead to a malignant phenotype of TNBC, and this result was consistent with the conclusion drawn from the survival analysis ( Ye et al, 2020 ). Additional research is necessary to determine the potential mechanisms that contribute to the interplay between GPER and ERRα in TNBC.…”
Section: Mechanism Of Gper In Tnbcsupporting
confidence: 91%
“…Ligands including E2 and bisphenol A were claimed to trigger GPER to promote migration and metastasis of TNBC cells [21][22][23] . E2 also induced the up-regulation of estrogenrelated receptor α expression via GPER activation, enhanced the migration and invasion of TNBC cells 55 . Increased GPER expression was observed at the invasive margin in some nests, implying that GPER activation may contribute to the invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…High GPER expression was also related to decreased outcomes, including the local RFS, DDFS, OS, and PFS in a Chinese cohort ( n = 249) 17 . In a retrospective TNBC study ( n = 199), GPER and estrogen-related receptor α (ERR-α) synergistically predicted poor patient outcomes 55 . In summary, studies seem to agree that GPER can mediate estrogen carcinogenesis and promote the progression of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study demonstrated that cytoplasmic ER was inversely associated to Ki67 LI in the ER-negative breast carcinoma. It is well recognized that ER signaling activation is lack in TNBC [ 29 ]. However, recently Contreras-Zarate et al found that estradiol induced BDNF/TrkB signaling in TNBC to promote brain metastases [ 4 ], and Girgert et al suggested that estradiol significantly increased cell proliferation of TNBC in vitro , along with the activation of Src, EGFR (epidermal growth factor receptor), Cyclin D1, and CREB (cAMP-responsive element binding) signaling [ 8 ].…”
Section: Discussionmentioning
confidence: 99%